Cryptocurrency Adoption in Indonesia: Economic Drivers Behind Behavioral Intentions Using UTAUT/2 - Triantara, Muhamad Ridwan; Halim, Rizal Edy (Yayasan Riset dan Pengembangan Intelektual, 2025)
The purpose of this study is to empirically examine the influence of constructs from the modified UTAUT/2 on behavioral intention to use cryptocurrency in Indonesia. The sampling technique employed non-probability sampling through an online questionnaire on a Likert scale of 1-6 and succeeded in getting 327 respondents. The research model with 12 hypotheses was tested using PLS-SEM (variance-based SEM). The results show that performance expectancy, effort expectancy, social influence and facilitating conditions have a positive effect on behavioral intention to use cryptocurrency. However, the influence of gender and age as moderating variables is not supported by existing data.